Liturgical music: Worship or war? - Kloppers, Elsabé (Hervormde teologiese studies, 1997)
The way we are affected by music in general and the role of association, as well as the way association influences the forming of criteria for the evaluation of music and how these criteria would apply to church music, are discussed. The essence of liturgy and the function of music, as part of the liturgy are established. The conclusion is made that 'variety' is the key for the renewal of liturgical singing.